Horizontal bone augmentation by means of guided bone regeneration - Benic, Goran I.; Hämmerle, Christoph H. F. (Periodontology 2000, 2014)
The development of bone augmentation procedures has allowed placement of dental implants into jaw bone areas lacking an amount of bone sufficient for standard implant placement. Thus, the indications for implants have broadened to include jaw regions with bone defects and those with a bone anatomy that is unfavorable for implant anchorage. Of the different techniques, the best documented and the most widely used method to augment bone in localized alveolar defects is guided bone regeneration. A large body of evidence has demonstrated the successful use of guided bone regeneration to regenerate missing bone at implant sites with insufficient bone volume and the long‐term success of implants placed simultaneously with, or after, guided bone regeneration. However, the influence of guided bone regeneration on implant survival and success rates, and the long‐term stability of the augmented bone, remain unknown. Many of the materials and techniques currently available for bone regeneration of alveolar ridge defects were developed many years ago. Recently, various new materials and techniques have been introduced. Many of them have, however, not been sufficiently documented in clinical studies. The aim of this review was to present the scientific basis of guided bone regeneration and the accepted clinical procedures. A classification of bone defects has been presented, aiming at simplifying the decision‐making process regarding the choice of strategy for bone augmentation. Finally, an outlook into actual research and the possible future options related to bone augmentation has been provided.